Dynamic evolution and network structure characteristics of the wellbeing eco-efficiency of cities in the Yellow River Basin, China - Wang, Meixia; Zheng, Qingyun; Liu, Li (Frontiers in Environmental Science, 2025)
The wellbeing eco-efficiency (WEE) is a core indicator for assessing the quality of regional ecological environment and the wellbeing of people’s livelihood. Clarifying its spatial and temporal dynamic evolution and network structure characteristics is crucial for promoting the ecological protection and high-quality development in the entire Yellow River Basin (YRB). Based on the panel data of 99 cities in the YRB from 2010 to 2022, the WEE is measured by introducing the ecological wellbeing into the evaluation system of eco-efficiency. The spatial-temporal dynamics, disparities, and their origins, as well as the structural attributes of the network, are investigated. The results showed that: First, The WEE in the YRB, upper, middle, and lower reaches have been improved, showing the stage characteristics of “steady growth-fluctuation decline-rapid growth,” and technological progress is the main driving force for efficiency growth. Second, the absolute difference of WEE in the whole and middle reaches shows an expanding trend, and the upper and lower reaches show a decreasing trend. The inter-regional differences and hypervariable density are the main sources of spatial differences. Third, the YRB has broken the geographical location restrictions and formed a multi-threaded complex network form. During the sample investigation period, the network scale and network agglomeration have been continuously enhanced, and the small-world network correlation effect is significant. Forth, regarding the small group network characteristics: the upper reaches’ WEE has a “wheeled” structure centered on Longnan; the middle reaches’ WEE forms a “chain” structure with Yulin, Xi’an, and Ankang as cores; and the lower reaches’ WEE exhibits a “dual-core multi-center radial” structure with Heze and Zhengzhou at its core, featuring significant two-way interactions.